Methyltransferase-Deficient Avian Flaviviruses Are Attenuated Due to Suppression of Viral RNA Translation and Induction of a Higher Innate Immunity - Wu, Xuedong; Zhang, Yuetian; Wang, Mingshu; Chen, Shun; Liu, Mafeng; Zhu, Dekang; Zhao, Xinxin; Wu, Ying; Yang, Qiao; Zhang, Shaqiu; Huang, Juan; Ou, Xumin; et al. (Frontiers in Immunology, 2021)
The 5’ end of the flavivirus genome contains a type 1 cap structure formed by sequential N-7 and 2’-O methylations by viral methyltransferase (MTase). Cap methylation of flavivirus genome is an essential structural modification to ensure the normal proliferation of the virus. Tembusu virus (TMUV) (genus Flavivirus) is a causative agent of duck egg drop syndrome and has zoonotic potential. Here, we identified the in vitro activity of TMUV MTase and determined the effect of K61-D146-K182-E218 enzymatic tetrad on N-7 and 2’-O methylation. The entire K61-D146-K182-E218 motif is essential for 2’-O MTase activity, whereas N-7 MTase activity requires only D146. To investigate its phenotype, the single point mutation (K61A, D146A, K182A or E218A) was introduced into TMUV replicon (pCMV-Rep-NanoLuc) and TMUV infectious cDNA clone (pACYC-TMUV). K-D-K-E mutations reduced the replication ability of replicon. K61A, K182A and E218A viruses were genetically stable, whereas D146A virus was unstable and reverted to WT virus. Mutant viruses were replication and virulence impaired, showing reduced growth and attenuated cytopathic effects and reduced mortality of duck embryos. Molecular mechanism studies showed that the translation efficiency of mutant viruses was inhibited and a higher host innate immunity was induced. Furthermore, we found that the translation inhibition of MTase-deficient viruses was caused by a defect in N-7 methylation, whereas the absence of 2’-O methylation did not affect viral translation. Taken together, our data validate the debilitating mechanism of MTase-deficient avian flavivirus and reveal an important role for cap-methylation in viral translation, proliferation, and escape from innate immunity.